Identification of Secretory Leukoprotease Inhibitor As an Endogenous Negative Regulator in Allergic Effector Cells - Matsuba, Shintaro; Yabe-Wada, Toshiki; Takeda, Kazuya; Sato, Tetsuya; Suyama, Mikita; Takai, Toshiyuki; Kikuchi, Toshiaki; Nukiwa, Toshihiro; Nakamura, Akira (Frontiers in Immunology, 2017)
Mast cells, basophils, and eosinophils are central effectors in allergic inflammatory disorders. These cells secrete abundant serine proteases as well as chemical mediators and cytokines; however, the expression profiles and functions of their endogenous inhibitors remain elusive. We found that murine secretory leukoprotease inhibitor (SLPI) is expressed in basophils and eosinophils but in not in mast cells. SLPI-deficient (Slpi-/-) basophils produce more cytokines than wild-type mice after IgE stimulation. Although the deletion of SLPI in basophils did not affect the release of chemical mediators upon IgE stimulation, the enzymatic activity of the serine protease tryptase was increased in Slpi-/- basophils. Mice transferred with Slpi-/- basophils were highly sensitive to IgE-mediated chronic allergic inflammation. Eosinophils lacking SLPI showed greater IL-6 secretion and invasive activity upon lipopolysaccharide (LPS) stimulation, and the expression of MMP-9 by these eosinophils was increased without stimulation. The absence of SLPI increases JNK1 phosphorylation at the steady state, and augments the serine phosphorylation of JNK1-downstream ETS transcriptional factor Elk-1 in eosinophils upon stimulation. Of note, SLPI interacts with a scaffold protein, JNK-interacting protein 3 (JIP3), that constitutively binds to the cytoplasmic domain of TLR4, suggesting that SLPI controls Elk-1 activation via binding to JIP3 in eosinophils. Mice transferred with Slpi-/- eosinophils showed the exacerbation of chitin-induced allergic inflammation. These findings show that SLPI is a negative regulator in allergic effector cells, and suggested a novel inhibitory role of SLPI in the TLR4 signaling pathways.